Splenic cyst abscess: report of a cese - Montenegro, Roxana (2003)
The authors report a rare case of a chronic splenic abscess in a 52 years old male patient, who had an incidental diagnosis of an asymptomatic calcified splenic cyst two years before. Admission history was of 12 months left upper quadrant pain as the sole symptom. After surgical intervention, a diagnosis of chronic splenic abscess or splenic pseudocyst was established with anatomopathological confirmation. The case characteristics are described and the literature is reviewed.